TRATEGIC PATHS FOR THE DEVELOPMENT OF ENTREPRENEURIAL ACTIVITY IN THE MILK AND DAIRY PRODUCTS MARKET - A. Lomakina (Вестник Северо-Кавказского федерального университета, 2022)
The development of the dairy industry is one of the priority courses of state policy in the agroindustrial complex (AIC) of Russia, as an increase in milk production in the country will provide a threshold indicator of the doctrine of food security. The aim of the study is to assess the state of the milk and dairy products market and determine the directions of its development. The paper provides an overview of the main development indicators of the dairy industry in Russia as a whole and the Stavropol Territory in particular, analyzes the main global development trends in the dairy production segment and their impact on the domestic dairy market